2003
DOI: 10.1029/2002ja009590
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous EISCAT Svalbard radar and DMSP observations of ion upflow in the dayside polar ionosphere

Abstract: [1] Regions where dayside field-aligned (FA) ion upflows occur are identified, and the relative occurrences and characteristics are compared. The study is based on $170 simultaneous events observed with the European Incoherent Scatter (EISCAT) Svalbard radar (ESR) and spacecraft from the DMSP. We found that ion upflows occur not only in the cusp and cleft (the low-altitude portion of the low-latitude boundary layer), which traditionally have been regarded as regions of ion upflow, but also in the region connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 34 publications
(36 reference statements)
6
68
0
Order By: Relevance
“…[34] Figure 6 shows a clear local correspondence between soft precipitation enhancements and increased electron temperature, consistent with previous observations and models showing soft precipitation to be the driver for ionospheric upflows [Caton et al, 1996;Su et al, 1999;Ogawa et al, 2003;Moen et al, 2004]. Figure 7 also shows a clear correspondence between BBELF activity and elevated ion temperature.…”
Section: Wave Activity and Ion Temperaturesupporting
confidence: 77%
See 1 more Smart Citation
“…[34] Figure 6 shows a clear local correspondence between soft precipitation enhancements and increased electron temperature, consistent with previous observations and models showing soft precipitation to be the driver for ionospheric upflows [Caton et al, 1996;Su et al, 1999;Ogawa et al, 2003;Moen et al, 2004]. Figure 7 also shows a clear correspondence between BBELF activity and elevated ion temperature.…”
Section: Wave Activity and Ion Temperaturesupporting
confidence: 77%
“…The former finding is in agreement with Seo et al [1997] who identified the anticorrelation of precipitating electron energy and ion up flux at low DE-2 satellite (850 -950 km) altitudes. Ogawa et al [2003] used DMSP and EISCAT to show that soft precipitation primarily drives ion upflow. Chaston et al [2006] used FAST data to investigate a cold ionospheric density cavity in the dayside auroral oval and found evidence of enhanced electric and magnetic field fluctuations, wave accelerated ions, and field-aligned downward directed electron fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yau et al (1988) parameterised the ionospheric ion outflow and found that the O + outflow rate increased exponentially with Kp as exp(0.5 Kp). Other studies that have shown a clear correlation between O + and geomagnetic activity are Peterson et al (2001), Cully et al (2003), and Kistler and Mouikis (2016). The O + density close to the mid-latitude magnetopause was shown by Bouhram et al (2005) to also increase exponentially with Kp.…”
Section: Introductionmentioning
confidence: 93%
“…Cold (< 1 eV) H + and O + outflows can thus dominate in both flux and density in the distant magnetotail lobes (Engwall et al, 2009). The cusps are regions which enable direct interaction between the magnetosheath and the ionosphere, leading to increased elec-tron temperatures and higher ion upflows as a consequence in the cusp ionosphere (Nilsson et al, 1996;Ogawa et al, 2003;Kistler et al, 2010). Ionospheric upflow is still gravitationally bound and needs further energisation in order to reach the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The exact relation between ionospheric upflow in the cusp as measured by incoherent scatter radar (e.g. Nilsson et al, 1996;Ogawa et al, 2003) and the more energized ions observed further out in the magnetosphere is still not clear. The further energization of ions of apparently ionospheric cusp origin and subsequent outflow is the subject of several recent studies; Valek et al (2002) used observations of isotropic magnetosheath-like ions in the dayside magnetosphere (i.e.…”
Section: Introductionmentioning
confidence: 99%